1982
DOI: 10.1111/j.1476-5381.1982.tb09340.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Purines and Noradrenaline by Ouabain and Potassium Chloride From Vascular Adrenergic Nerves

Abstract: Release of [3H]‐noradrenaline and 3H‐purine by ouabain (10−4m) or high KCl (50 mm) was investigated in the superfused rabbit pulmonary arterial segment preincubated with [3H]‐noradrenaline or [3H]‐adenosine. Ouabain elicited a delayed large contraction and a parallel [3H]‐noradrenaline efflux. These were substantially inhibited by Ca2+‐free medium or preincubation with 6‐hydroxydopamine (30 μg/ml, 30 min). Ouabain caused an 3H‐purine efflux which was slower than the [3H]‐noradrenaline efflux. This was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In our experimental conditions it is unlikely that these routes of Ca influx were operative. In many types of vascular smooth muscle treated with cardiac glycosides or low K solutions the contractions are partially mediated by noradrenaline released from adrenergic nerve endings Katsuragi & Su, 1982;Hayashi & Park, 1984). However, experimental evidence demonstrates that, in guinea-pig aortic strips, the mechanical response to the above stimuli is the result of a purely myogenic mechanism Karaki et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental conditions it is unlikely that these routes of Ca influx were operative. In many types of vascular smooth muscle treated with cardiac glycosides or low K solutions the contractions are partially mediated by noradrenaline released from adrenergic nerve endings Katsuragi & Su, 1982;Hayashi & Park, 1984). However, experimental evidence demonstrates that, in guinea-pig aortic strips, the mechanical response to the above stimuli is the result of a purely myogenic mechanism Karaki et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for release of NA and ATP as cotransmitters from sympathetic nerves supplying rabbit pulmonary arteries was reported 30 years ago (Katsuragi and Su, 1982). An important advance was made when it was shown that excitatory junctional potentials recorded in the smooth muscle of rat intrapulmonary arteries in response to sympathetic nerve stimulation were mediated by ATP (Inoue and Kannan, 1988).…”
Section: E Vasculaturementioning
confidence: 99%
“…Evidence for release of NA and ATP as cotransmitters from sympathetic nerves supplying rabbit pulmonary arteries was recognized (Katsuragi and Su, 1982;Mohri et al, 1993). An important advance was made when it was shown that EJPs recorded in the smooth muscle of rat intrapulmonary arteries in response to sympathetic nerve stimulation were mediated by ATP (Inoue and Kannan, 1988).…”
Section: J Pulmonary Vesselsmentioning
confidence: 99%